2021
DOI: 10.1136/bmjopen-2020-043328
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of a self-assessment questionnaire concerning symptoms and impairment in urinary tract infections: the UTI-SIQ-8

Abstract: ObjectivesTo validate the urinary tract infection-Symptom and Impairment Questionnaire (UTI-SIQ-8), a questionnaire that consists of four items to assess the symptom severity for dysuria, urgency, frequenc, and low abdominal pain and four items to assess the resulting impairment of activity by UTIs.DesignProspective observation study.SettingGerman primary care practices.ParticipantsAn unselected population of women with UTI. Women could participate online via a web application for smartphones, smartwatches and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…There have been some questionnaires for patients with AUC, such as the Urinary Tract Infection Symptom Assessment, [8] Acute Cystitis Symptom Score, [9] and Urinary Tract Infection Symptom and Impairment Questionnaire. [10] Although these questionnaires have been shown to exert excellent diagnostic performance in primary care, they were designed to elicit essential information for diagnosis, but not for comprehensive LUTS assessment. [8][9][10] Furthermore, to avoid ambiguous terms and clarify symptom differences, the CLSS questionnaire was used in the study as a patient-reported outcome measure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been some questionnaires for patients with AUC, such as the Urinary Tract Infection Symptom Assessment, [8] Acute Cystitis Symptom Score, [9] and Urinary Tract Infection Symptom and Impairment Questionnaire. [10] Although these questionnaires have been shown to exert excellent diagnostic performance in primary care, they were designed to elicit essential information for diagnosis, but not for comprehensive LUTS assessment. [8][9][10] Furthermore, to avoid ambiguous terms and clarify symptom differences, the CLSS questionnaire was used in the study as a patient-reported outcome measure.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Although these questionnaires have been shown to exert excellent diagnostic performance in primary care, they were designed to elicit essential information for diagnosis, but not for comprehensive LUTS assessment. [8][9][10] Furthermore, to avoid ambiguous terms and clarify symptom differences, the CLSS questionnaire was used in the study as a patient-reported outcome measure. For instance, dysuria refers to not only pain or discomfort but also difficulty voiding and is not specific to the symptom site (bladder and urethra).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants completed a validated eight-item symptom questionnaire (UTI-SIQ-8) to assess symptom severity and UTIrelated activity impairment due to each symptom [16]. Each item was scored from 0 (none) to 4 (very strong).Duration of J o u r n a l P r e -p r o o f symptoms, previous UTI episodes, comorbidity, medication, and sociodemographic data were collected at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, PROMs are valuable tools. For uncomplicated UTIs, several disease-specific instruments have been developed and validated, assessing symptom burden [ 6 , 7 ], the impairment of daily activities [ 6 , 8 ], and HRQoL [ 6 ]. The selection of a PROM is guided by content-related considerations, including the construct to be measured and the target population, but it is also essential to consider the quality of the measurement properties of available instruments.…”
Section: Introductionmentioning
confidence: 99%